Back to basics: does decentralization improve health system performance? Evidence from Ceará in north-east Brazil - Sarah Atkinson; Dave Haran
OBJECTIVE: To examine whether decentralization has improved health system performance in the State of Ceará, north-east Brazil. METHODS: Ceará is strongly committed to decentralization. A survey across 45 local (município) health systems collected data on performance and formal organization, including decentralization, informal management and local political culture. The indicators for informal management and local political culture were based on prior ethnographic research. Data were analysed using analysis of variance, Duncan's post-hoc test and multiple regression. FINDINGS: Decentralization was associated with improved performance, but only for 5 of our 22 performance indicators. Moreover, in the multiple regression, decentralization explained the variance in only one performance indicator; indicators for informal management and political culture appeared to be more important influences. However, some indicators for informal management were themselves associated with decentralization but not any of the political culture indicators. CONCLUSION: Good management practices in the study led to decentralized local health systems rather than vice versa. Any apparent association between decentralization and performance seems to be an artefact of the informal management, and the wider political culture in which a local health system is embedded strongly influences the performance of local health systems.